2015
DOI: 10.1103/physreve.92.053014
|View full text |Cite
|
Sign up to set email alerts
|

Capillary imbibition of aqueous foams by miscible and nonmiscible liquids

Abstract: When put in contact with a large liquid drop, dry foams wick owing to surface-tension-driven flows until reaching equilibrium. This work is devoted to the dynamics of this imbibition process. We consider imbibition of both wetting or nonwetting liquid, by putting the dry foam into contact either with the foaming solution that constitutes the foam or with organic oils. Indeed, with the appropriate choice of surfactants, oil spontaneously invades the liquid network of the foam without damaging it. Our experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…It is possible that capillary action helps replenish the water lost in the foam by drawing from the water underneath. Mensire et al [38] conducted experiments with foam solution or olive oil placed under a very dry foam (expansion ratio 833-14285) and monitored the rise of liquid into the foam against gravity due to capillary action. Mensire found that the liquid rose 5.5 mm upwards into the foam's Plateau borders in 200 s for monodisperse foams with an expansion ratio of 1408 and a bubble diameter of 1.8 mm.…”
Section: Room Temperature Experimentsmentioning
confidence: 99%
“…It is possible that capillary action helps replenish the water lost in the foam by drawing from the water underneath. Mensire et al [38] conducted experiments with foam solution or olive oil placed under a very dry foam (expansion ratio 833-14285) and monitored the rise of liquid into the foam against gravity due to capillary action. Mensire found that the liquid rose 5.5 mm upwards into the foam's Plateau borders in 200 s for monodisperse foams with an expansion ratio of 1408 and a bubble diameter of 1.8 mm.…”
Section: Room Temperature Experimentsmentioning
confidence: 99%
“…CAPB+SLES+Mac [31] Olive Oil -4±2 CAPB+SLES [32] Sunflower Oil -2±2 SDS [29] Rapeseed Oil 3±3 NaDBS [12] Benzene -0.9 SDS [21] Tetralin 3.…”
Section: Foaming Solutionmentioning
confidence: 99%
“…Oil has been injected from a single point source into a single PB [35] or into a foam [45]. Other geometries where a flat oil slick is connected to a 2D or 3D aqueous foam have also been reported [30,31]. To describe these experiments, the drainage equation, originally derived for pure aqueous foams [55,77,78,79,80,81,82,83] , is numerically solved taking into account gravity effect.…”
Section: Biliquid Foams: Dynamics Of Oil Flowmentioning
confidence: 99%
“…[39][40][41] Imbibition of liquid into a foam occurs owing to the capillary pressure of the Plateau border, and comparison with the gravity effect is the key to imbibition on earth. 42,43 Microgravity has been investigated in liquid imbibition to minimize the effect of gravity, [44][45][46][47][48][49][50] in which the bubbles are very stable and coarsening or coalescence does not occur. 50 Imbibition can be explained by a diffusion-like process and the wetting front is proportional to the square root of time.…”
Section: Introductionmentioning
confidence: 99%